The Suitability of Reading Materials in English Textbook Used for Junior High School to the 2013 Curriculum - Sri Okta Bela; Albert Albert (Modality Journal: International Journal of Linguistics and Literature, 2021)
AbstrakBuku teks merupakan salah satu sumber bahan ajar yang digunakan guru dalam mengajarkan bahan bacaan. Di Indonesia, penggunaan buku teks sebagai bahan ajar untuk kegiatan membaca secara intensif   harus sesuai dengan kurikulum  2013 sebagai kurikulum yang berlaku saat ini.   Penelitian ini bertujuan untuk mengetahui kesesuaian bahan ajar membaca di dalam buku teks dengan kurikulum 2013 untuk aspek relevansi, konsistensi, dan kecukupan. Teknik kuantitatif digunakan dalam penelitian ini. Data penelitian dikumpulkan dari dua buku teks bahasa Inggris, buku bahasa Inggris kelas 7 untuk Sekolah Menengah Pertama yang diterbikan oleh  Kementerian Pendidikan dan Kebudayaan, dan Yudhistira. Sampel diambil dengan menggunakan purposive sampling yang dipilih sesuai dengan pilihan peneliti dan tujuan penelitian. Adapun instrumen penelitian yang digunakan yaitu lembar penilaian untuk buku teks. Penelitian ini menemukan bahwa dari aspek relevansi dalam buku  When English Rings Bell yang diterbitkan oleh Kementerian Pendidikan dan Kebudayaan dan buku teks yang diterbitkan Yudhistira dikategorikan “Cukup” dengan persentase masing-masing 76%. Selanjutnya dari aspek konsistensi, buku When English Rings Bell  dikategorikan “Buruk” dengan persentase 16%,  sedangkan pada buku 2 dikategorikan “Baik” dengan persentase 82%. Terakhir, dari aspek kecukupan, baik buku  When English Rings Bell yang diterbitkan Kementerian Pendidikan dan Kebudayaan, maupun Yudhistira menempati kategori yang sama dikategorikan “cukup” dengan persentase masing-masing 61%. Disimpulkan, berbeda dengan aspek konsistensi, kedua buku teks bahasa Inggris yang diteliti ini dikategorikan cukup untuk aspek relevansi dan kecukupan.  Artinya, kedua buku teks bahasa Inggris memiliki kelebihan dan kekurangannya dalam konteks kesesuaianya  dengan kurikulum 2013.Kata kunci: Bahan Ajar Membaca, Buku Teks Bahasa Inggris, Kurikulum 2013AbstractTextbook is one of the sources of teaching materials used by teachers in teaching reading skills. In Indonesia, the use of textbooks as teaching materials for intensive reading activities must be in accordance with the 2013 curriculum as the current curriculum. This study aims to determine the suitability of reading teaching materials in textbooks with the 2013 curriculum for aspects of relevance, consistency, and adequacy. Quantitative techniques were used in this study. The research data were collected from two English textbooks, the 7th grade English book for Junior High School published by the Ministry of Education and Culture, and Yudhistira. Samples were taken using purposive sampling which were selected according to the researcher's choice and research objectives. The research instrument used was an assessment sheet for textbooks. This study found that from the aspect of relevance, the book When English Rings Bell published by the Ministry of Education and Culture and the textbook published by Yudhistira were categorized as “Enough” with a percentage of 76% each. In the aspect of consistency, the book When English Rings Bell was categorized as "Bad" with a percentage of 16%, while in book published by Yudhistira was categorized as “good”  with a percentage of 82%. Lastly, in the aspect of adequacy, both the text books published by the Ministry of Education and Culture, and Yudhistira occupied the same category, it was “enough” with a percentage of 61% each. In conclusion, in contrast to the aspect of consistency, the two English textbooks studied were categorized as adequate for the aspects of relevance and adequacy. That is, both English textbooks have their strengths and weaknessesin the context of their suitability with the 2013 curriculum.Keywords: Reading Material ,English Texbook,Curriculum 2013